Pengaruh Peringkat Obligasi terhadap Keputusan Pendanaan, Keputusan Investasi, dan Nilai Perusahaan (Studi pada Perusahaan-perusahaan Sektor Property dan Real Estate di BEI Periode 2016-2020) - Anugrah Rahma Danny; Yulia Efni; Fitri Fitri (Bahtera Inovasi, 2023)
This study aims to determine the effect of bond ratings on funding decisions, investment decisions, and firm value in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The population in this study amounted to 78 companies, but after selecting the sample using purposive sampling technique, a sample of 12 companies was obtained. Secondary data was obtained from the IDX's official website, fact book, company's official website, and PEFINDO. Hypothesis testing is done by path analysis and Sobel test. The results of this study indicate that bond ratings have a positive influence on funding decisions. Bond ratings have a positive influence on investment decisions. Bond ratings have a positive effect on firm value. Funding decisions have no effect on firm value. Investment decisions have a positive influence on firm value. Bond ratings do not have an indirect effect on firm value through funding decisions as an intervening variable. Bond rating has an indirect influence on firm value through investment decisions as an intervening variable.